Analysis of the Pb0.30CaxSryTiO3 ternary system: The effect of Ca2+ and Sr2+ cations on the electrical properties of PbTiO3 - Gouveia, Amanda Fernandes; Ribeiro, Lara Kelly; Assis, Marcelo; Longo, Elson; Andrés, Juan; Pontes, Fenelon Martinho Lima (Eclética Química, 2022)
Powder and thin films of the Pb0.30Ca0.10Sr0.60TiO3 (PCST 30/10/60) and Pb0.30Ca0.60Sr0.10TiO3 (PCST 30/60/10) ternary system were synthetized by the polymeric precursor method and the thin films deposited on the Si/SiO2/Ti/Pt substrate. The effects of the Sr2+ and Ca2+ cations substitutions on the electrical and structural properties of the PbTiO3 were characterized by X-ray diffraction, Infrared, and Raman spectroscopy. Theoretical calculations were performed using the CRYSTAL06 program associated with the density functional theory and the B3LYP functional hybrid. Structural and electronic properties of the system were analyzed. The band gap values calculated for the PCST 30/10/60 and PCST 30/60/10 models were 3.35 and 3.41 eV, respectively. The results showed an evolution to a greater symmetry in the direction to the cubic SrTiO3 structure and the phase transition was characterized by the Curie temperature dependence. The broad bands above FE-PE phase transition temperature suggest a phase transition diffuse type. It is explained by a local symmetry disorder due to a higher Sr2+ and Ca2+ cations concentration in the PbTiO3 host lattice.